Vitamin C Causes a Much-Pronounced Damange to DNA in Presence of Cd2+ but not in Presence on Zn2+ or Ag+. Why? - Huq, Fazlul; Hossain, Zahed (Asian Journal of Chemistry, 2010)
Super oxide dismutase and rhodamine assays carried out in the present study show that free radicals were produced from the interaction between molecular oxygen and 1: 1 mixture of cadmium(II) acetate and ascorbate or 1 : 1 mixture of silver(I) acetate and ascorbate. Molecular modelling analysis combined with pH measurement shows that in presence of Cd2+, ascorbic acid essentially acts as a strong polyprotic acid whereas in presence of Ag+, it acts as a monoprotic acid. It is believed that the binding of ascorbate with the metal ions Cd2+ and Ag+ causes the molecular activation, which is more susceptible to attack, by molecular oxygen. Reactive oxygen species produced from the interaction between activated ascorbate species and molecular oxygen damage DNA.